Encapsulation of cardiac stem cells in superoxide dismutase‐loaded alginate prevents doxorubicin‐mediated toxicity. (30th December 2011) - Liu, Ting Chu Ken; Ismail, Siti; Brennan, Orlaith; Hastings, Conn; Duffy, Garry P.
Abstract Anthracyclines are powerful drugs available for the treatment of neoplastic diseases. Unfortunately, these chemotherapy agents cause cardiomyopathy and congestive heart failure. Doxorubicin (DOX) is a widely used anthracycline and evidence indicates that DOX‐induced cardiotoxicity can be viewed as a stem cell disease, whereby the formation of reactive oxygen species (ROS) by DOX is seen to predominantly hinder cardiac stem cell (CSC) regenerative capability. Acute, early‐onset and late‐onset cardiotoxicity have been described and this may be reversible by the local administration of CSCs, which regenerate myocardial tissue and rescue the failing heart. CSCs are, however, particularly sensitive to oxidative stress and die rapidly by apoptosis in such adverse conditions. Therefore, this study aims to enhance CSC survival by encapsulation in an alginate hydrogel formulation containing superoxide dismutase (SOD), a reactive oxygen species scavenger. Cell survival was qualitatively and quantitatively assessed by fluorescent microscopy and assays measuring metabolic activity, cell viability, cytotoxicity and apoptosis. CSCs were cultured in DOX‐conditioned cell culture medium and displayed reduced live cell numbers as well as high levels of apoptosis. Encapsulation of CSCs in alginate alone failed to prevent apoptosis. Encapsulation in SOD‐loaded alginate reduced apoptosis to near‐normal levels, whilst metabolic activity was returned to baseline. In conclusion, this study demonstrates that encapsulation of CSCs in SOD‐loaded alginate hydrogel enhances CSC survival in the presence of DOX, raising the possibility of its application as a novel therapy for the treatment of acute and early onset DOX‐induced cardiotoxicity. Copyright © 2011 John Wiley & Sons, Ltd.